Circulating Protein Biomarkers in Systemic Sclerosis Related Pulmonary Arterial Hypertension: A Review of Published Data - Hickey, Peter M.; Lawrie, Allan; Condliffe, Robin (Frontiers in Medicine, 2018)
Pulmonary arterial hypertension (PAH) develops in 7-12% of patients with systemic sclerosis (SSc) and is associated with a 3 year survival of 52%. Early detection by screening is therefore recommended for all patients with SSc. Historically, screening has been performed using echocardiography and measurement of gas transfer. More recently the DETECT protocol, using a combination of biomarkers (including N-terminal pro-brain natriuretic peptide) and clinical parameters, has been developed. The optimal method of screening for PAH with high sensitivity and specificity is, however, not clear. Protein expression differences between different SSc disease phenotypes have been reported, and include alterations in concentration of NT-proBNP, endoglin, soluble vascular endothelial growth factor receptor 1, placenta growth factor, growth differentiation factor-15, vascular endothelial growth factor alpha, resistin-like molecule beta, and soluble thrombomodulin. This review summarises the current knowledge of these protein changes in patients with SSc and PAH.